Interactions Between Gut Microbiota and Acute Restraint Stress in Peripheral Structures of the Hypothalamic-Pituitary-Adrenal Axis and the Intestine of Male Mice - Vagnerová, Karla; Vodička, Martin; Hermanová, Petra; Ergang, Peter; Šrůtková, Dagmar; Klusoňová, Petra; Balounová, Kateřina; Hudcovic, Tomáš; Pácha, Jiří (Frontiers in immunology, 2019)
The gut microbiota play an important role in shaping brain functions and behavior, including the activity of the hypothalamus-pituitary-adrenocortical (HPA) axis. However, little is known about the effect of the microbiota on the distinct structures (hypothalamus, pituitary, and adrenals) of the HPA axis. In the present study, we analyzed the influence of the microbiota on acute restraint stress (ARS) response in the pituitary, adrenal gland, and intestine, an organ of extra-adrenal glucocorticoid synthesis. Using specific pathogen-free (SPF) and germ-free (GF) male BALB/c mice, we showed that the plasma corticosterone response to ARS was higher in GF than in SPF mice. In the pituitary, stress downregulated the expression of the gene encoding CRH receptor type 1 (Crhr1), upregulated the expression of the Fkbp5 gene regulating glucocorticoid receptor sensitivity and did not affect the expression of the proopiomelanocortin (Pomc) and glucocorticoid receptor (Gr) genes. In contrast, the microbiota downregulated the expression of pituitary Pomc and Crhr1 but had no effect on Fkbp5 and Gr. In the adrenals, the steroidogenic pathway was strongly stimulated by ARS at the level of the steroidogenic transcriptional regulator Sf-1, cholesterol transporter Star and Cyp11a1, the first enzyme of steroidogenic pathway. In contrast, the effect of the microbiota was significantly detected at the level of genes encoding steroidogenic enzymes but not at the level of Sf-1 and Star. Unlike adrenal Sf-1, the expression of the gene Lrh-1, which encodes the crucial transcriptional regulator of intestinal steroidogenesis, was modulated by the microbiota and ARS and this effect differed between the ileum and colon. The findings demonstrate that gut microbiota have an impact on the response of the pituitary, adrenals and intestine to ARS and that the interaction between stress and the microbiota during activation of glucocorticoid steroidogenesis differs between organs. The results suggest that downregulated expression of pituitary Pomc and Crhr1 in SPF animals might be an important factor in the exaggerated HPA response of GF mice to stress.
Keywords: fosfoproteiny; kortikosteron; Pro-Opiomelanocortin; střevní mikroflóra; Pituitary Gland; Corticosterone; Mice, Inbred BALB C; steroidní akutní regulační protein; Phosphoproteins; myši inbrední BALB C; zvířata; fyzické omezení; Colon; Pituitary-Adrenal System; Gastrointestinal Microbiome; mice; Hypothalamo-Hypophyseal System; regulace genové exprese; hypofýza; kolon; ileum; Gene Expression Regulation; enzym štěpící postranní řetězce cholesterolu; Receptors, Corticotropin-Releasing Hormone; nadledviny; Stress, Psychological; receptory hormonu uvolňujícího kortikotropin; mužské pohlaví; Cholesterol Side-Chain Cleavage Enzyme; acute restraint stress; Restraint, Physical; gut microbiota; Steroidogenic Factor 1; psychický stres; HPA axis; systém hypotalamus-hypofýza; CRF Receptor, Type 1; pro-opiomelanokortin; receptor CRF typu 1; Animals; systém hypofýza - nadledviny; Ileum; Adrenal Glands; extra-adrenal glucocorticoid synthesis; intestine; Steroidogenic Acute Regulatory Protein; steroidogenní faktor 1; Male; germ-free